2008
DOI: 10.1152/physrev.00028.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-Adrenoceptor Signaling in Skeletal Muscle: Implications for Muscle Wasting and Disease

Abstract: The importance of beta-adrenergic signaling in the heart has been well documented, but it is only more recently that we have begun to understand the importance of this signaling pathway in skeletal muscle. There is considerable evidence regarding the stimulation of the beta-adrenergic system with beta-adrenoceptor agonists (beta-agonists). Although traditionally used for treating bronchospasm, it became apparent that some beta-agonists could increase skeletal muscle mass and decrease body fat. These so-called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
356
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(389 citation statements)
references
References 473 publications
7
356
0
12
Order By: Relevance
“…There are a few studies reporting on direct innervation of skeletal muscle fibers by nonmyelinated, noradrenergic fibers (Barker & Saito, 1981; Lynch & Ryall, 2008), suggesting that sympathetic actions on skeletal muscle are at least partially mediated by neural mechanisms. It has been reported that sympathetic neurons coinnervate several targets in muscle, including blood vessels, motor neurons, muscle fibers, and NMJs (Khan et al., 2016; Rudolf et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies reporting on direct innervation of skeletal muscle fibers by nonmyelinated, noradrenergic fibers (Barker & Saito, 1981; Lynch & Ryall, 2008), suggesting that sympathetic actions on skeletal muscle are at least partially mediated by neural mechanisms. It has been reported that sympathetic neurons coinnervate several targets in muscle, including blood vessels, motor neurons, muscle fibers, and NMJs (Khan et al., 2016; Rudolf et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that β2-agonists induce muscle hypertrophy in many species [10][11][12][13][14][15][16][17][18][19][20][21][22] . Experiments in mice lacking β1-AR, β2-AR, or both subtypes, have demonstrated that clenbuterol-induced effects, such as muscle hypertrophy, are mediated by β2-AR 10) .…”
Section: Anabolic and Metabolic Adaptations To β2-agonists And Exercisementioning
confidence: 99%
“…Experiments in mice lacking β1-AR, β2-AR, or both subtypes, have demonstrated that clenbuterol-induced effects, such as muscle hypertrophy, are mediated by β2-AR 10) . β2-agonists promote muscle growth by stimulating protein synthesis and reducing protein degradation [11][12][13] . Furthermore, the hypertrophic response to β2-agonists is known to appear more frequently in fast-twitch muscles [11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Anabolic and Metabolic Adaptations To β2-agonists And Exercisementioning
confidence: 99%
See 2 more Smart Citations